Characterisation of cytochrome P450 isoenzyme activity in sheep liver and placental microsomes. (January 2023) - Meakin, Ashley S.; Amirmostofian, Marzieh; Darby, Jack RT.; Holman, Stacey L.; Morrison, Janna L.; Wiese, Michael D.
Abstract: Introduction: Drug metabolism during pregnancy is a complex process that involves maternal, placental and fetal sites of metabolism. Indeed, there is a lack of clarity provided from drug metabolism in human pregnancy due to ethical limitations. Large animal models of human pregnancy provide an opportunity to quantify activity of phase 1 drug metabolism mediated by cytochrome P450 (CYP) enzymes in the maternal, placental, and fetal compartments. Herein, we have validated a comprehensive assay to quantify maternal, placental, and fetal CYP activity. Methods: Isolated microsomes from sheep maternal liver, placenta, and fetal liver (140d gestation, term = 150d) were incubated with CYP-specific probe drugs to quantify the activity of CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1 and CYP3A. Inhibition studies were performed to validate specificity of probe drugs. The validated assay was developed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: CYP1A2, CYP2B6, CYP2C8, CYP2C19, CYP2D6, CYP2E1 and CYP3A were active in maternal liver. In contrast, only CYP1A2, CYP2C8 and CYP2D6 were active in the placenta, whereas CYP2B6, CYP2C8 and CYP2D6 were active in the fetal liver. Of the placental-specific CYPs validated, CYP1A2 increased in type A compared with type D placentomes, whereas CYP2C8 activity increased in type B compared with type A and C. Discussion: This study has established conditions for compartment-specific CYP activity in the sheep maternal-placental-fetal unit using a validated and standardised experimental workflow. Compartment- and placentome type-specific CYP activity are important considerations when examining drug metabolism in the maternal-placental-fetal unit and in determining the impact of pregnancy complications. Highlights: A validated workflow to quantify CYP 1A2, 2C8 and 2D6 activity in sheep placenta was generated. CYP1A2 is active in placenta but not fetal liver; 2C8 and 2D6 are active in both placenta and fetal liver. CYP1A2 activity increased in placentome type A compared to D; CYP2C8 decreased in placentomes A and C compared to type B. This methodology will serve as a tool to examine placental-specific metabolism in sheep models of pregnancy complications.